Legal capacity in online loan transactions (The study on legal personal liability theory) - Supeno Supeno (Annals of Justice and Humanity, 2022)
Purpose: This study aims to determine how the law views the aspect of legal capacity in conducting online loan transactions and the exact aspect of legal capacity in the context of the Legal Personal Liability theory. Research Methodology: This research employed a blended aspect by using a statutory approach, case approach, and theoretical approach. Results: The author claims that the understanding of legal capacity in the legal aspect that measures age and status is inappropriate, and legal capacity must be interpreted not only in terms of age or status but it must also be interpreted more broadly, involving the ability of the parties to make decisions and the ability of the parties to carry out what has been decided by prioritizing legal personal liability. Limitations: The author argues that positioning Legal personal Liability is very important in Loan transactions. Legal capacity should not be merely interpreted in terms of age and status aspect but it should take broad interpretation because related awareness to implement the agreement has been made. The restrictions of legal capacities based on the law in Indonesia are to be analyzed using the theory of Legal Personal Liability. Contribution:  This study is expected to educate and be useful to lecturers, legal practitioners, loan business practitioners, policymakers, the financial service authority, and all the members of the public performing loan transactions.